Caveola-vesicle complexes of Plasmodium vivax and Plasmodium cynomolgi: large-scale aggregation and structure of PHIST-positive vesicles in late schizont-infected red blood cells - Lawrence H. Bannister; Anton R. Dluzewski; Esmeralda V. S. Meyer; Stacey A. Lapp; Mary R. Galinski (Malaria Journal)
Abstract Background Numerous caveola-vesicle complexes (CVCs) form around the surface of Plasmodium vivax and Plasmodium cynomolgi infected erythrocytes during the asexual cycle. They include a 95 kDa protein in both species, the Plasmodium helical interspersed subtelomeric (PHIST) protein (PHIST/CVC-8195) located at the cytoplasmic face of CVC vesicles and tubules. The functions and detailed structure of CVCs are poorly understood, although they are essential for parasite survival. In this study, electron and immuno-electron microscopy were used to explore structural changes to CVCs during the final phase of parasite maturation, when they may lose their importance to metabolic function. Methods Blood with maturing parasite-infected erythrocytes was collected by venipuncture from Saimiri boliviensis and rhesus macaque monkeys infected with P. vivax and P. cynomolgi, respectively. Platelets and leukocytes were removed from the blood, and trophozoite- and schizont-infected erythrocytes were purified and concentrated. The parasitized RBCs were fixed in 2.5% v/v glutaraldehyde for morphological electron microscopy study or 2% v/v paraformaldehyde and 0.075% v/v glutaraldehyde for immuno-electron microscopy; sections were immuno-stained with rabbit anti-PHIST antibodies detected with protein A-conjugated to 10 nm gold. Results Caveola-vesicle complexes, present along the periphery of trophozoite-infected erythrocytes, are dismantled in late-stage schizont-infected cells, releasing vesicles and tubules which aggregate as extensive PHIST-positive clusters within the infected cells. The clusters persist beyond the egress of merozoites, amongst the debris of the infected cells. The walls of vesicles and tubules are basket-like frameworks of fine filaments. Vesicle lumens also contain clusters of filaments and spheroidal spinous particles. Conclusions Caveolae-vesicle complex integrity is stage-specific. The CVC numbers are maximal in trophozoite and early schizont phases, and they are dismantled prior to merozoite egress when caveolae disappear and their vesicles and tubules are released to aggregate within the infected erythrocytes. This timing indicates that CVC activities are primarily related to the parasite’s earlier trophic metabolism. Detailed study shows that vesicles and tubules have a unique structure which provides data relevant to the question of their function(s). The persistence of vesicle clusters after red cell lysis is also significant for the pathology of malaria.